Model for The Development of Basic Values of Science and Environmental Awareness Through The Potential of Teachers' Teaching Styles, Learning Styles and Students' Thinking Styles at The First Middle School in Cirebon City - Wahidin Wahidin; Sulfikar Sallu (STKIP Singkawang, 2022)
Until now, teachers have not focused on developing basic science values, scientific thinking styles and environmental awareness of students in schools. Teachers in schools are preoccupied with pursuing curriculum targets for cognitive academic achievement. So the indicator of student success is measured only by academic achievement. Meanwhile, critical thinking skills, creative, innovative and students' awareness of the environment are rarely measured as learning outcomes. In the science education curriculum at LPTKs, this learning achievement has not been clearly defined. The purpose of this study is to examine the model of developing basic science values and environmental awareness through the teaching style of teachers, learning styles and thinking styles of junior high school students in Cirebon City. The research method used is the mix method. Samples were taken purposively and simple random from junior high school students who were the research targets. Data collection techniques were carried out by observation, in-depth interviews with teachers and tests on class VIII students using thinking skills test instruments and questionnaires. The results showed that the teacher's teaching style became a mental model for students in building thinking patterns, developing basic science values, and students' awareness of the surrounding environment. The science education curriculum in the LPTK environment needs to be reviewed, especially regarding the learning outcomes for the competence of prospective science teachers related to the competence to teach thinking skills and students' awareness.